Computation of Electric Field and Thermal Properties of 3-Phase Cable - K. Rajagopala K. Rajagopala; K. Panduranga Vittal; Hemsingh Lunavath (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
In this paper the electric field distribution, potential distribution and temperature distribution in a 3-phase underground cable in common ground enclosure is analyzed and presented. Unlike 3-Phase screened cable the stress distribution in a belted cable is not radial. A 3-phase high voltage power cable buried in soil can be used to investigate its electrical and thermal properties. In the present study the voltage distribution of an underground cable of 132 kV is analyzed using FEM and its ampacity and temperature distribution is calculated by analytical method. Further their performance parameter is verified using Comsol Multiphysics software. The results obtained using comsol software is also compared with the results of CSM model which is obtained through literature review.